Retrospective analytical 10 years study of male mammography - Tondare, Antappa Shantappa; Vare, Ajay Aasaram (International Journal of Research in Medical Sciences, 2017)
Background: Awareness of early breast cancer detection in women through mammography study (diagnostic as well as screening) was planned by Mangal Medi Centre through referral doctors for diagnostic and direct approach to cross society (screening) with an early detection of breast cancer. But incidentally or coincidentally so many males underwent the Mammography. So those reports were analysis retrospective. Methods: Retrospective study of 92 men who underwent mammography procedures co-incidentally, during well planned study of early detection of breast cancer for women through mammography in last 10 years in one of the NGO named Mangal Medi Center Aurangabad. Those findings were analysed and hereby are presented, in which age varied as low as 11 years and as high as 77 years. Results: Even though relatively seems to be small in number, is having lot of significance to that, as only few researcher carry out this type of study and Men hardly go for Mammography and even Medical fraternity hardly refers male for mammography. A total of 92 patients that too Men underwent mammography (X-ray base technique to detect early breast lesions and mainly breast cancer) along with high frequency Sonography of each and every patient were carried out. Conclusions: Our study of 92 patients nearly showed the 6 patients having very high suspicions of malignancy means nearly 8% (Even though breast cancer in male is usually of 1%). So this retrospective analytical study concludes that even though routine mammography screening (In female every year) is not required in male but definitely it will be an a useful tool in patients having any type of complain related with breast like pain, enlargement or both, may help a lot to diagnose breast lesions like calcification, gynaecomastia and breast cancer in early stage (as a general rule breast cancer in male is diagnosed in late stage due to myth that breast cancer is not seeing in male, lack of self-awareness and coming in late stage with larger tumour size resulting you higher morbidity and mortality.